Cu‐Catalyzed Aerobic Oxidative Coupling of Tetrahydro‐β‐carbolines with Indoles. Issue 24 (25th June 2021) - Chen, Haijun; Qiao, Panpan; Luo, Yining; Hu, Jing; Gao, Yu
Abstract: A copper‐catalyzed aerobic oxidative coupling reaction of tetrahydro‐β‐carbolines (THβCs) with indoles is reported for the first time. This room‐temperature catalytic strategy offers an efficient synthesis of the complex scaffold with an excellent chemoselectivity profile under mild reaction conditions. Abstract : A copper‐catalyzed aerobic oxidative coupling reaction of tetrahydro‐β‐carbolines (THβCs) with indoles is reported for the first time. This room‐temperature catalytic strategy offers an efficient synthesis of the complex scaffold with an excellent chemoselectivity profile under mild reaction conditions.